2019
DOI: 10.1002/adfm.201901012
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Engineered Synthesis of Ultrathin Hexagonal and Monoclinic GaTe Flakes and Phase Transition Study

Abstract: GaTe is an important III-VI semiconductor with direct bandgap; thus, it holds great potential in the field of optoelectronics. Although it is known that GaTe can exist both in monoclinic and hexagonal phases, current studies are still exclusively restricted to the monoclinic phase of two dimensional (2D) GaTe owing to the difficulty in the fabrication of 2D hexagonal GaTe. Both monoclinic and hexagonal GaTe are demonstrated in this work, which can be selectively synthesized via a physical vapor deposition meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 34 publications
8
74
2
1
Order By: Relevance
“…However, under appropriate growth conditions, thick hexagonal GaTe flakes can be also obtained. Yu et al recently demonstrated the phase-controlled synthesis of monoclinic and hexagonal GaTe using conventional physical vapor deposition technique [ 112 ]. They found that growth temperature is the key factor for phase control of GaTe flakes, and h-GaTe flakes are intended to be stable under relatively low deposition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, under appropriate growth conditions, thick hexagonal GaTe flakes can be also obtained. Yu et al recently demonstrated the phase-controlled synthesis of monoclinic and hexagonal GaTe using conventional physical vapor deposition technique [ 112 ]. They found that growth temperature is the key factor for phase control of GaTe flakes, and h-GaTe flakes are intended to be stable under relatively low deposition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Vapor deposition synthesis has been proven to be one of the most reliable methods in achieving high quality crystalline 2D materials. [ 24–26 ] In this study, a spaced‐confine PVD technique is applied to grow ultrathin InI. The deposition process is made up of an upstream in which a low melting point InI granule (351 °C) was put in, and a downstream zone where clean fluorophlogopite mica ([KMg 3 (AlSi 3 O 10 )F 2 ]) is arranged on a u‐shape glass tube (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Few‐layer GaTe flakes and thin films have been obtained experimentally since the late 90′s, [40] but have been studied most intensively in the past few years [41–46] . Many technics can be used for the synthesis of nano‐sized objects.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the initially acquired hexagonal thin films turn into monoclinic structures upon annealing at 500–700 °C, depending on their thickness. In this regard, the formation temperature may be the main factor for the phase control of GaTe films [45] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation